Curse of Eelgrass Bog - Averling, Mary (New York Razorbill, 2024)
"Nothing about Kess Pedrock's life is normal. Not her home (she lives in her family's Unnatural History Museum), not her interests (hunting for megafauna fossils and skeletons), and not her best friend (a talking demon's head in a jar named Shrunken Jim). But things get even stranger than usual when Kess meets Lilou Starling, the new girl in town. Lilou comes to Kess for help breaking a mysterious curse--and the only clue she has leads straight into the center of Eelgrass Bog. Everyone knows the bog is full of witches, demons, and possibly worse, but Kess and Lilou are determined not to let that stop them. As they investigate the mystery and uncover long-buried secrets, Kess begins to realize that the curse might hit closer to home than she'd ever expected, and she'll have to summon all her courage to find a way to break it before it's too late"--
112885
Keywords: Siblings -- Juvenile fiction; Museums -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Lesbians -- Juvenile fiction; Secrecy -- Juvenile fiction; Secrets -- Fiction; Fantasy; LGBTQ+ youth; Lesbian fiction; LGBTQ+ fiction; Fantasy fiction